Issues & ethics in the helping professions - Gerald Corey; Marianne Schneider Corey; Cindy Corey (Boston, Massachusetts : Cengage Learning, 2019)
Up-to-date and comprehensive, this practical best seller provides students with the basis for discovering their own guidelines for helping within the broad limits of professional codes of ethics and divergent theoretical positions. Respected authors Gerald Corey, Marianne Corey, and Cindy Corey raise what they consider to be central issues, present a range of diverse views on the issues, discuss their position, and provide opportunities for students to refine their thinking and develop an informed position. With new material in every chapter and an emphasis on critical thinking, Issues and Ethics in the Helping Professions, 10th Edition, is useful for students as well as practicing professionals. This edition features MindTap®, the digital learning solution that helps instructors engage and transform today's students into critical thinkers and successful helpers
Keywords: Counseling ethics; Professional ethics; Psychotherapy Moral and ethical aspects